Factors relating to self-management behaviors of patients with chronic obstructive pulmonary diseases in Bangladesh - Sormin Sultana Parvin (Prince of Songkla University, 2014)
Thesis (M.N.S. (Nursing Science))--Prince of Songkla University, 2013